2020
DOI: 10.1186/s12944-020-01376-7
|View full text |Cite
|
Sign up to set email alerts
|

Combined extracts of Moringa oleifera, Murraya koeingii leaves, and Curcuma longa rhizome increases energy expenditure and controls obesity in high-fat diet-fed rats

Abstract: Background: LI85008F is a proprietary combination of leaf extracts of Moringa oleifera, Murraya koeingii, and extract of Curcuma longa rhizome. This herbal extract combination is an effective weight loss supplement for overweight and obese subjects. The present study aimed to investigate the thermogenic potential of the LI85008F in high-fat diet (HFD)-induced obese Sprague Dawley rats. Methods: Seven rats received a regular diet (RD), and twenty-one rats received a high-fat diet (HFD) for 56 days. On day 28, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The western blot assays were performed following the methodology described earlier with some modifications ( 23 ). Briefly, an equal amount of cell or tissue lysate proteins was resolved using 7.5 or 10% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE).…”
Section: Methodsmentioning
confidence: 99%
“…The western blot assays were performed following the methodology described earlier with some modifications ( 23 ). Briefly, an equal amount of cell or tissue lysate proteins was resolved using 7.5 or 10% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE).…”
Section: Methodsmentioning
confidence: 99%
“…A study using an herbal extract combination comprised of 60% MO leaves ethanolic extract in doses of 100 and 250 mg/kg BW for 28 days significantly reduced BW gain, total body fat mass, the fat cell size of inguinal and epididymal white adipose tissue (WAT), liver weight, and hepatic triglycerides and increased resting energy expenditure (REE) and fat oxidation on obese rats. The decrease of fat cell size and mass in supplemented obese rats was due to the increase energy metabolism through browning of WAT, the increase of expression of UCP1, and down-regulation expression of key adipogenic marker proteins (PPARγ, C/EBPα, CD36, aP-2α, and perilipin ( Kundimi et al, 2020 ). However, they found that this herbal combination did not substantially affect the interscapular BAT fat mass of obese rats.…”
Section: Role Of Mo In Cardiovascular Diseasesmentioning
confidence: 99%
“…On the other hand, MO leaves have been recorded to elevate the plasma insulin such as growth factor I (IGF-I) [271] insulin [144] and leptin hormones [42,184] leading to inhibiting adipogenesis [180,272]. On the contrary, others recorded its ability to reduce serum leptin [152,181,273,274] leading to an increase in the energy expenditure and controlling obesity [275].…”
Section: Moringa Oleifera and Hormonesmentioning
confidence: 99%